Branding Kota Pinta Pada Teknologi Komunikasi Tangerang Live - Abdul Basit; Adie Dwiyanto Nurlukman (Universitas Lancang Kuning, 2021)
Tangerang City Government is trying to ready a smart city to provide convenience in all respects, one of which is the communication technology currently being used is the Tangerang LIVE application. Indirectly this can create good branding for the Tangerang City government. The Tangerang LIVE application has not been running as it should be, so the purpose of this research is to use this application to answer the needs and desires of the people of Tangerang City. This research was conducted with quantitative methods; this method can be answered the study's purpose. Like what the government runs this smart city through this application, the population is around Tangerang City. The study results found that smart city branding influences communication technology in the Tangerang Live application. Public services and delivery of information developed through digital communication by the Tangerang City Government are more integrated, monitored, effective, and efficient for the community